Evaluation of fruit extracts of six Turkish Juniperus species for their antioxidant, anticholinesterase and antimicrobial activities - TOPÇU, GÜLAÇTI; Ozturk, Mehmet; Tumen, Ibrahim; Ugur, Aysel; Aydogmus-Ozturk, Fatma; Topcu, GÜLAÇTI (My University, 2011)
BACKGROUND: Juniperus L. (Cupressaceae) species are mostly spread out in the Northern Hemisphere of the world, and some of them are used as folkloric medicines. The fruits of some species are eaten. Since oxidative stress is one of the reasons for neurodegeneration and is associated with the Alzheimer-s disease (AD), the extracts prepared from the fruits of six Juniperus species were screened for their antioxidant activity. Therefore, the extracts were also evaluated against acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), which are chief enzymes in the pathogenesis of AD. In addition, antimicrobial activity was also evaluated.